Rivastigmine Reduces “Likely to Use Methamphetamine” in Methamphetamine-Dependent Volunteers - De La Garza, R. (2011)
We previously reported that treatment with the cholinesterase inhibitor rivastigmine (3 mg, PO for 5 days) significantly attenuated “Desire for METH”. Given that higher dosages of rivastigmine produce greater increases in synaptic ACh, we predicted that 6 mg should have more pronounced effects on craving and other subjective measures. In the current study, we sought to characterize the effects of short-term exposure to rivastigmine (0, 3 or 6 mg) on the subjective and reinforcing effects produced by administration of methamphetamine (METH) in non-treatment-seeking, METH-dependent volunteers. This was a double-blind, placebo-controlled, crossover study. Participants received METH on day 1, and were then randomized to placebo or rivastigmine on day 2 in the morning and treatment continued through day 8. METH dosing was repeated on day 6. The data indicate that METH (15 and 30 mg), but not saline, increased several positive subjective effects, including “Any Drug Effect”, “High”, “Stimulated”, “Desire METH”, and “Likely to Use METH” (all p’s<0.0001). In addition, during self-administration sessions, participants were significantly more likely to choose METH over saline (p<0.0001). Evaluating outcomes as peak effects, there was a trend for rivastigmine to reduce “Desire METH” (p=0.27), and rivastigmine significantly attenuated “Likely to Use METH” (p=0.01). These effects were most prominent for rivastigmine 6 mg when participants were exposed to the low dose (15 mg, IV), but not high dose (30 mg, IV), of METH. The self-administration data reveal that rivastigmine did not alter total choices for METH (5 mg, IV/choice). Overall, the results indicate some efficacy for rivastigmine in attenuating key subjective effects produced by METH, though additional research using higher doses and longer treatment periods is likely needed. These data extend previous findings and indicate that cholinesterase inhibitors, and other drugs that target acetylcholine systems, warrant continued consideration as treatments for METH dependence.